E-commerce Impact on Accounting Efficiency in MSMEs - Br Tumanggor, Menda Winarti; Pasaribu, Windi; gulo, Septina Joe Sephine; Laia, Tafaogo; lombu, Nurhayanti; Butar Butar, Dwi Fany Fransiska Dewi (INSPIRETECH GLOBAL INSIGHT, 2025)
Purpose of the study: This study aims to comprehensively analyze the impact of e-commerce adoption on the efficiency of accounting systems among MSMEs in Medan Kota District, Indonesia, and to identify key factors mediating this relationship. Materials and methods: Employing a quantitative research design, data were collected from 120 MSMEs using stratified random sampling. Structured questionnaires and adapted Motor Competency Assessment tools were utilized to measure e-commerce adoption and accounting system efficiency. Statistical analyses included descriptive statistics, Pearson correlation, and path regression analysis to determine the strength and direction of relationships. Results: The results reveal a significant positive correlation (r = 0.62, p < 0.01) between e-commerce adoption and accounting system efficiency. Path regression analysis indicates that e-commerce adoption explains 38% of the variance in accounting efficiency (R² = 0.38, p < 0.01). Further analysis suggests that digital literacy and organizational readiness moderate this relationship. Conclusions: E-commerce adoption substantially improves the efficiency of accounting systems in MSMEs, with digital literacy and organizational readiness serving as important enabling factors. These findings underscore the need for targeted interventions to support digital transformation in MSMEs.